Social Development Approach to the Promotion of Human Rights - TENDENGU, Tariro; TENDENGU, Lameck (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2022)
Traditional models of development have been criticised for not considering issues bordering on security rights, legal rights, political rights and cultural rights as major aspects contributing to socio economic and sustainable development of countries. Development is a concept and a multifaceted phenomenon. It involves social, political and economic progress facilitated by quick technological evolution. Todaro (2012) states that development is a multidimensional process involving the reorganisation and reorientation of the entire economic and social systems. Various models have been put forward trying to define and shape development at a global level. Some of them are classical while others are contemporary. Traditional models of development include the Linear Stages Growth model influenced by the writings of Harold Domar and W. Rostow in the 1950s, modernisation theory and the dependency theories. These models emphasize development along economic lines where attention is given to increased savings, economic investment and acquisition of appropriate technology which lead to structural transformation of the economy and production. This paper therefore seeks to argue on the contention that traditional models of development have long been criticised for lack of attention to human rights and inadvertently contributing to human rights violations (Androff, 2006). This contention will be examined with reference to the role played by the Social Development Approach (SDA) to the promotion of human rights in Zimbabwe.